IMPLEMENTASI KEBIJAKAN PENYELENGGARAAN PELAYANAN PUBLIK DI KANTOR CAMAT JAILOLO KABUPATEN HALMAHERA BARAT - DOWONGI, ALVONCE (JURNAL ADMINISTRASI PUBLIK, 2014)
ABSTRACT This research comes from problem that policy of public services inparticular related to implementation UU 25 nomor tahun 2009 about public serviceshas not impleminted by western halmahera district goverment specially in subdistrictjailolo office. This cordition indicated that has not enough quantity and quality theservices employer of human resources office building, facilities and equipment forbacking up services has not enough.This research used qualitative’s approximation with application description method.Data and information gathered by the interview technics to is informan, andcompleted with observation technic and dokumentation, then analyzed withapproximation interaktion-description technics.There by, inferential that problem can impeded implementation public services insubdistrict jailolo office has not enough quantity and quality of human ( employer )public services. There fore, suggested a goverment of western halamhera need involveservices employer in exercise functional on the services sector and pay attention hargeof falility and infrastructure with equipment for backing up service, especiallyreallocate building subdistrict office to representative location and to completingfacility with equipment for backing up services so as to recipient service receiver feelcontented on the given services from subdistrict jailolo’s goverment.Keywords : Policy Implementation, public service